Perception and adoption of social media marketing by food and beverage MSMEs in Iloilo - Balofiños, Jeriesa Mae E.; Bañares, Alyssa Julienne A.; Balofiños, Jeriesa Mae E. (2024.)
There is a growing trend in the utilization of digital marketing specifically social media marketing in the digital landscape of businesses nowadays. In this study, the perception and adoption of social media marketing by Food and Beverage MSMEs in Iloilo City was evaluated by its current utilization, the factors affecting its usage, and the relationship between the utilization and performance of the Food and Beverage MSMEs. This study was conducted to provide insight of the effectiveness of social media marketing and for MSMEs to make more tailored marketing strategies. A survey was conducted among the Food and beverage MSMEs in Iloilo with 47 respondents who were selected through convenience sampling. The results showed that most respondents use social media marketing with Facebook as their main platform. among the factors influencing the use of social media marketing, knowledge has a significant direct influence to the perceived usefulness, technical expertise influences as well the perceived ease of use, and traditional preference influences both the perceived usefulness and perceived ease of use of social media marketing. With this, perceived usefulness affects the attitude towards the use of social media marketing in terms of the willingness to invests. And this attitude also affects the actual use in terms of the time length of use, which also affects the actual performance of MSMEs in terms of follower growth. When MSMEs are equipped with relevant information and sufficient resources, they are more inclined to embracing social media marketing as a viable solution to their marketing needs.
Thesis (BSBA-Marketing). -- [Iloilo City] : University of the Philippines Visayas - College of Management, July 2024.